2007
DOI: 10.3892/ijmm.20.3.329
|View full text |Cite
|
Sign up to set email alerts
|

The antitumor activities of curcumin and of its isoxazole analogue are not affected by multiple gene expression changes in an MDR model of the MCF-7 breast cancer cell line: Analysis of the possible molecular basis

Abstract: Abstract.We examined the effects of curcumin and of its isoxazole analogue MR 39 in the MCF-7 breast cancer cell line and in its multidrug-resistant (MDR) variant MCF-7R. In comparison with MCF-7, MCF-7R lacks estrogen receptor α (ERα) and overexpressess P-glycoprotein (P-gp), different IAPs (inhibitory of apoptosis proteins) and COX-2. Through analyses of the effects on cell proliferation, cycling and death, we have observed that the antitumor activity of curcumin and of the more potent (approximately two-fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
40
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 20 publications
4
40
1
Order By: Relevance
“…Based on the »hard and so (Lewis) acids and bases« (HSAB) concept that electrophiles a ack the coumarine ring (19), the eight heterocyclic amines, isoxazoles and thiazoles, were derivatized to obtain diazonium ions which would be further used as electrophiles to a ack the coumarine ring at position 3. Isoxazole and thiazole substituents were used based on the literature data pointing to the antiproliferative and tumour vascular-disrupting activity of their derivatives (20)(21)(22)(23), with isoxazole and thiazole rings being important pharmacophores. Their anticancer eff ects were demonstrated in vivo (23) and in vitro (24-26) using various cancer cell lines, including breast cancer cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the »hard and so (Lewis) acids and bases« (HSAB) concept that electrophiles a ack the coumarine ring (19), the eight heterocyclic amines, isoxazoles and thiazoles, were derivatized to obtain diazonium ions which would be further used as electrophiles to a ack the coumarine ring at position 3. Isoxazole and thiazole substituents were used based on the literature data pointing to the antiproliferative and tumour vascular-disrupting activity of their derivatives (20)(21)(22)(23), with isoxazole and thiazole rings being important pharmacophores. Their anticancer eff ects were demonstrated in vivo (23) and in vitro (24-26) using various cancer cell lines, including breast cancer cells.…”
mentioning
confidence: 99%
“…Isoxazole and thiazole substituents were used based on the literature data pointing to the antiproliferative and tumour vascular-disrupting activity of their derivatives (20)(21)(22)(23), with isoxazole and thiazole rings being important pharmacophores. Their anticancer eff ects were demonstrated in vivo (23) and in vitro (24-26) using various cancer cell lines, including breast cancer cells. Hence, a superior cellular eff ect was expected in comparison with 4-hydroxycoumarin as a reference.…”
mentioning
confidence: 99%
“…Curcumin has been shown to exhibit antioxidant, anti-inflammatory, antimicrobial, and anticarcinogenic activities. Several studies suggested that cyclocurcumin compound were found to be inhibiting proliferation of breast cancer cells [26][27][28].…”
Section: Cyclocurcuminmentioning
confidence: 99%
“…Poma et al [66] have also examined the effects of curcumin and compound 63 in the MCF-7 breast cancer cell line, and in its multi-drug resistant variant MCF-7R, which lacks estrogen receptor alpha (ER-) and exhibits over-expression of P-glycoprotein (P-gp), IAP (inhibitory of apoptosis proteins) and COX-2 proteins. It was observed that the anti-tumor activity of curcumin and compound 63 is equivalent in the MDR cell line.…”
Section: Modifications Of Diketo Functionality-das and Coworkersmentioning
confidence: 99%